2019
DOI: 10.3390/nu11102266
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Difficulties and Risk for Early Breastfeeding Cessation

Abstract: Although breast milk is the normative feeding for infants, breastfeeding rates are lower than recommended. We investigated breastfeeding difficulties experienced by mothers in the first months after delivery and their association with early breastfeeding discontinuation. We conducted a prospective observational study. Mothers breastfeeding singleton healthy term newborns at hospital discharge were enrolled and, at three months post-delivery, were administered a questionnaire on their breastfeeding experience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
160
4
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 32 publications
12
160
4
21
Order By: Relevance
“…In multiparas, absence of breast complications at 1 month postpartum was associated with subsequent exclusive breastfeeding. Although this association supported previous studies [34,35], we did not ascertain the reason why it was observed only in multiparas. In general, primiparas experienced more breast complications than multiparas [36], as observed in the present study.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In multiparas, absence of breast complications at 1 month postpartum was associated with subsequent exclusive breastfeeding. Although this association supported previous studies [34,35], we did not ascertain the reason why it was observed only in multiparas. In general, primiparas experienced more breast complications than multiparas [36], as observed in the present study.…”
Section: Discussioncontrasting
confidence: 68%
“…Women with lower breastfeeding selfe cacy were also reportedly more likely to perceive milk insu ciency [9,29]. Such a perception has been described as a factor related to cessation of exclusive breastfeeding [30]. The perception of milk insu ciency itself was not assessed in our study because this concept was supposed to be contained in questions of the BSES-SF.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, inadequate breast milk supply and maternal loss of feeding initiative due to pain, poor perinatal mood or even work can delay early breastfeeding. [5][6][7] Despite perinatal support such as home care, gynecologists, nurses and lactation consultants, the early stages of breastfeeding are still much more difficult than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…Poor breastfeeding position may have an effect on the mother's wellbeing and exacerbate issues through a negative impact on the infant's positioning, latch and duration of breastfeeding events [6]. According to a study [7], around 70.3% of mothers experienced breastfeeding di culties, including cracked nipples, perception of insu cient amount of milk, pain, and fatigue. And it was painful for many respondents to hold their infant to breastfeed, pick up their infant, and sit comfortably to breastfeed.…”
Section: Introductionmentioning
confidence: 99%